Understanding the career decision making of university students enrolled in STEM disciplines. (July 2021) - Bennett, Dawn; Knight, Elizabeth; Bawa, Sherry; Dockery, Alfred M
This study investigated why university students choose to major in Science, Technology, Engineering, Mathematics, and Medicine/health (STEM(M)) disciplines, and how their study and career-related confidence compares with that of their peers. The study engaged 12, 576 students enrolled at Australian universities. The findings suggest that STEM(M) students' career decision making is guided by their interest in the subject and their intentions to help people. Within the STEM(M) cohort, students in medicine and health were more confident in their career decision making than either their STEM or non-STEM(M) peers. Of interest, they were less aware of alternative career pathways and less prepared to reorient their careers should this be necessary. Female students reported greater confidence than male students in their career decision making, career identity, and career commitment. Implications include the need for career narratives beyond the STEM industries and for career development initiatives that are mindful of disciplinary and gendered differences.